Porphyry, Steuco and the Journey of Oracles between Symphony and Conflict - Tissi, Lucia Maddalena (Zeitschrift für antikes Christentum, 2020)
In this paper I explore the reasons why oracular texts of the past are considered to be useful to demonstrate a cultural symphony and how the perception of them changed in space and time. Moreover, I investigate how oracles worked as means of unity, agreement and cohesion in a society risking fragmentation and division. Specifically, I analyse Porphyry’s oracular collection De philosophia ex oraculis haurienda (transmitted indirectly) and Agostino Steuco’s major work, De perennia philosophia, published in 1540. Despite living in different historical eras, Porphyry and Steuco—I argue—seem to look for a kind of cultural symphony and to return to oracular wisdom as a response to a perceived and real threat (Christian religion for the first, Protestant Reform for the second). Their responses to the threat show various points of contact: against the risk of oblivion, they re-use and recover pre-fabricated sources of knowledge drawn from the past or the present, in order to address the challenges of their time with the aid of an established, “perennial” theological tradition. While the response provided by Porphyry against threats can be regarded as an elitist and exclusionary project, Steuco proposes, in his symphonic and propagandistic system, a real reductio ad unum (una religio, una scientia, unus Deus).